2016
DOI: 10.1111/jam.13189
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial peptide aureocin A53 as an alternative agent for biopreservation of dairy products

Abstract: Taken together, the results confirmed that aureocin A53 has potential to be used as a food preservative, representing an alternative to the use of nisin in biopreservation of dairy products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
4
6
0
Order By: Relevance
“…Lacticin Q displays strong bioactivity even at nanomolar concentrations whereas many other non-leaderless bacteriocins are active at a relatively higher concentration ( Fujita et al, 2007 ). Although some leaderless bacteriocins are produced by a number of strains that are often associated with pathogenicity and having structural similarity with hemolytic peptides and toxins (i.e., aureocin A53 and A70 are produced by S. aureus ), these leaderless bacteriocins have been demonstrated to have no cytotoxic and hemolytic activities, thus underlining the safety of their application ( Fagundes et al, 2016a , b ). Similar observation was manifested by enterocin DD14 (identical to enterocins 7 and MR10) when it was evaluated for its cytotoxicity against intestinal epithelial cell line IPEC-1 ( Caly et al, 2017 ).…”
Section: Applications Challenges and Prospectsmentioning
confidence: 99%
“…Lacticin Q displays strong bioactivity even at nanomolar concentrations whereas many other non-leaderless bacteriocins are active at a relatively higher concentration ( Fujita et al, 2007 ). Although some leaderless bacteriocins are produced by a number of strains that are often associated with pathogenicity and having structural similarity with hemolytic peptides and toxins (i.e., aureocin A53 and A70 are produced by S. aureus ), these leaderless bacteriocins have been demonstrated to have no cytotoxic and hemolytic activities, thus underlining the safety of their application ( Fagundes et al, 2016a , b ). Similar observation was manifested by enterocin DD14 (identical to enterocins 7 and MR10) when it was evaluated for its cytotoxicity against intestinal epithelial cell line IPEC-1 ( Caly et al, 2017 ).…”
Section: Applications Challenges and Prospectsmentioning
confidence: 99%
“…As a result, thucin A1 exhibited no hemolytic activity and cytotoxicity, even at concentrations much higher than its MIC values against a variety of indicator bacteria. In addition, recent studies have suggested that many leaderless bacteriocins, such as aureocin A53, aureocinA70 and toyoncin, can effectively inhibit or eliminate foodborne pathogens in skim milk, and possess desirable features to be used as food preservatives [ 1 , 42 , 50 ]. In the present study, we also observed that thucin A1 effectively inhibited or eliminated foodborne pathogens B. cereus and L. monocytogenes in skim milk.…”
Section: Discussionmentioning
confidence: 99%
“…Food pathogenic or spoilage bacteria pose serious threats to food quality and human health [ 1 3 ]. Chemical preservatives generally have certain detrimental effects, and therefore consumers show increasing demand for safer, healthier and natural biopreservatives [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, our results serve as a proof of principle. There are different types of LLBs, such as aureocin A53 ( 41 , 42 ) and weissellicin YM ( 43 ), and mature peptides from other nonmodified bacteriocins can also be the candidates for LLB-phage design. In addition to many choices of LLBs, there are an almost countless number of phages, meaning that in the future, it may be possible to produce any number of LLB-phages which can be designed to efficiently control different types of bacterial contamination in different settings.…”
Section: Discussionmentioning
confidence: 99%